2014
DOI: 10.1007/s11906-014-0458-4
|View full text |Cite
|
Sign up to set email alerts
|

Yes! Sex Matters: Sex, the Brain and Blood Pressure

Abstract: The role of the brain in sex differences in hypertension is known to be important especially with regards to the effects of circulating sex hormones. A number of different brain regions important for regulation of sympathetic outflow and blood pressure express estrogen receptors (ER), ERα and ERβ. Estradiol, acting predominantly via the ERα, inhibits angiotensin II activation of area postrema and subfornical organ neurons and inhibits reactive oxygen generation which is required for the development of Angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…In young male mice, but not cycling young female mice, systemic low-dose AngII-infusion results in a slowly developing increase in blood pressure (Girouard et al 2009, Li et al 2008, Marques-Lopes et al 2015a, Marques-Lopes et al 2014, Marques-Lopes et al 2015b, Pinkerton & Stovall 2010, Tiwari et al 2009, Van Kempen et al 2015b, Xue et al 2013, Xue et al 2005). However, slow-pressor AngII-infusion induces hypertension in OVX mice that model surgical menopause (Hay et al 2014, Xue et al 2013) and in aged rodents (Fortepiani et al 2003, Marques-Lopes et al 2015b, Tiwari et al 2009) that model the acyclicity (Nelson et al 1995) seen in post-menopause. Using a mouse model of Accelerated Ovarian Failure (AOF) that uniquely recapitulates hormonal changes seen in human menopause (Van Kempen et al 2014, Van Kempen et al 2011), we showed that the susceptibility to slow-pressor AngII hypertension begins at emerges at a timepoint that mimics perimenopause (i.e., when estrogens are present but erratically fluctuating) [9].…”
Section: Sex Differences Beyond the Hippocampus: Some Examplesmentioning
confidence: 99%
“…In young male mice, but not cycling young female mice, systemic low-dose AngII-infusion results in a slowly developing increase in blood pressure (Girouard et al 2009, Li et al 2008, Marques-Lopes et al 2015a, Marques-Lopes et al 2014, Marques-Lopes et al 2015b, Pinkerton & Stovall 2010, Tiwari et al 2009, Van Kempen et al 2015b, Xue et al 2013, Xue et al 2005). However, slow-pressor AngII-infusion induces hypertension in OVX mice that model surgical menopause (Hay et al 2014, Xue et al 2013) and in aged rodents (Fortepiani et al 2003, Marques-Lopes et al 2015b, Tiwari et al 2009) that model the acyclicity (Nelson et al 1995) seen in post-menopause. Using a mouse model of Accelerated Ovarian Failure (AOF) that uniquely recapitulates hormonal changes seen in human menopause (Van Kempen et al 2014, Van Kempen et al 2011), we showed that the susceptibility to slow-pressor AngII hypertension begins at emerges at a timepoint that mimics perimenopause (i.e., when estrogens are present but erratically fluctuating) [9].…”
Section: Sex Differences Beyond the Hippocampus: Some Examplesmentioning
confidence: 99%
“…In the brain cortex, ERα mediates neuroprotection during hypoxic/ischemic insults . ERα and ERβ reduce arterial blood pressure through the sympathetic nuclei in the brainstem and hypothalamus . In the model of angiotensin II‐induced hypertension, ERα in the suprafornical organ controls arterial blood pressure .…”
Section: Introductionmentioning
confidence: 99%
“…slow-pressor) increase in sympathetic tone and blood pressure [712]. However, slow-pressor AngII infusion induces hypertension in ovariectomized mice that model surgical menopause [12, 13] and in aged rodents [8, 10, 14] that model the acyclicity [15] seen in postmenopause. Unfortunately, neither of these approaches has been able to elucidate potential mechanisms related to ovarian hormone irregularity and decline that contribute to perimenopausal hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In young females, normal estrogen production and estrous cycling may play a key role in attenuating AngII-induced hypertension [12, 13] . Posttranscriptional gene silencing studies have revealed that these protective effects of estrogen on hypertension and ROS production critically involve estrogen receptor (ER) β, but not ERα, in the PVN [33] .…”
Section: Introductionmentioning
confidence: 99%